Addressing Violence through Critical Multicultural Education in an EFL Class (2020)
ABSTRACT: This action research project reports the possibilities offered by a critical multicultural approach to address the issue of violence in an English class with 7th graders in Marinilla, Colombia. The project had three stages in which participants reflected on violent manifestations at their homes, school and town. Furthermore, some participants conducted an online campaign to raise awareness about violence in their community. I collected data from class discussions journal notes and students' artifacts. The findings revealed to some extent the empowerment from some participants who took actions to transform the violent realities in their context. Furthermore, the project may have contributed to develop participants' critical multicultural awareness evident in more respectful interactions and collaborative work.